PENGARUH FAKTOR LINGKUNGAN KERJA DAN FAKTOR INDIVIDU TERHADAP PRESTASI KERJA KARYAWAN PADA PT.POS INDONESIA (Persero) KANTOR AREA II PADANG (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2016)
This research is measure the influence of environmental factors and individual factors on employee performance on PT.Pos Indonesia (Persero) Office Area II Padang. This study aims to determine the influence of environmental factors, organizational factors and individual factors on employee performance on PT.Pos Indonesia (Persero) Office Area II Padang. This research is a descriptive study associative. The population in this study were all employees of PT. Pos Indonesia (Persero) Office Area II Padang. The sampling technique used is total sampling. The analytical tool used is a validity test, reliability test, normality test, multicolinearity test, multiple linear regression, t-test, f, and test the coefficient of determination (R2). Results from this study are: a significant difference between the individual factors on employee performance on PT.Pos Indonesia (Persero) Office Area II Padang. And the influence of environment on employee performance on PT.Pos Indonesia (Persero) Office Area II Padang